Optimization of Sailcloth materials for better performance - Thein, Win. (2012)
Sailing is a well-established sport and a way to enjoy leisure time in modern days. There are three main types of recreational sailing, namely, racing, cruising and amateur sailing. Even though sail makers had made their own recommendations for different purposes, the brochures are full of compliments about their sail. Also, there has not yet been any study done to critically evaluate the types of sailcloth fabrics. Hence, the purpose of this paper is to investigate the fabric materials used for sailcloth and to recommend an optimum material suitable for each purpose.